Upgrading coagulation with hollow-fibre nanofiltration for improved organic matter removal during surface water treatment. (1st February 2016) - Köhler, Stephan J.; Lavonen, Elin; Keucken, Alexander; Schmitt-Kopplin, Philippe; Spanjer, Tom; Persson, Kenneth
Abstract: Rising organic matter concentrations in surface waters in many Nordic countries require current drinking water treatment processes to be adapted. Accordingly, the use of a novel nanofiltration (NF) membrane was studied during a nine month period in pilot scale at a large drinking water treatment plant in Stockholm, Sweden. A chemically resistant hollow-fibre NF membrane was fed with full scale process water from a rapid sand filter after aluminum sulfate coagulation. The combined coagulation and NF process removed more than 90% of the incoming lake water dissolved organic carbon (DOC) (8.7 mg C L −1 ), and 96% of the absorbance at 254 nm (A254) (0.28 cm −1 incoming absorbance). Including granulated active carbon GAC) filter, the complete pilot plant treatment process we observed decreases in DOC concentration (8.7–0.5 mg C L −1 ), SUVA (3.1–1.7 mg −1  L m −1 ), and the average nominal molecular mass (670–440 Da). Meanwhile, water hardness was practically unaffected (<20% reduction). Humic substances (HS) and biopolymers were almost completely eliminated (6510–140 and 260 to 10 μg C L −1 respectively) and low molecular weight (LMW) neutrals decreased substantially (880–190 μg C L −1 ). Differential excitation emission matrices (EEMs), which illustrate the removal of fluorescing organic matter (FDOM) over a range of excitation and emission wavelengths, demonstrate that coagulation removed 35 ± 2% of protein-like material and 65 ± 2% of longer emission wavelength, humic-like FDOM. The subsequent NF treatment was somewhat less selective but still preferentially targeted humic-like FDOM (83 ± 1%) to a larger extent than protein-like material (66 ± 3%). The high selectivity of organic matter during coagulation compared to NF separation was confirmed from analyses with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS), and liquid chromatography with organic carbon detection (LC-OCD), as coagulation exclusively targeted oxidized organic matter components while NF removed both chemically reduced and oxidized components. DOC removal and change in DOC character in the GAC filters showed marked differences with slower saturation and more pronounced shifts in DOC character using NF as pre-treatment. Fluorescence derived parameters showed a similar decrease over time of GAC performance for the first 150 days but also indicated ongoing change of DOM character in the post NF GAC filtrate over time even after LC-OCD indicated steady state with respect to outgoing carbon. During our trial iron concentrations were low (<30 ppb) and thus A254 could be directly related to the concentration of HS (R 2  = 0.9). The fluorescence derived freshness index (β:α) proved to be an excellent variable for estimating the fraction of HS present in all samples. Given the recommended limit of 4 mg L −1 for chemical oxygen demand (COD) for Swedish drinking water, coagulation will need to be supplemented with one or more treatment steps irrespective whether climate change will lead to drier or wetter conditions in order to maintain sufficient DOC removal with the current increasing concentrations in raw waters. Graphical abstract: Highlights: A newly developed NF membrane was evaluated over 9 months using a pilot plant. Coagulation removes (>500 Da, HS) terrestrial (FI = 1.4). NF removes range of DOC (350–500 Da) and properties ( C o s, w ¯ = − 0.07, FI = 1.65). Fluorescence parameters and correlations are reliable, fast and comparably cheap. Longer lake water retention reduces amount of hydrophobic DOC and thus lower DOC removal.